In-vitro investigation of factors affecting the fate of dry powders in the lung - Cingolani, Emanuela (2017)
The popularity of dry powder inhalers (DPIs) to deliver drugs to the lungs is constantly increasing thanks to their advantages over nebulisers and pressurised metered dose inhalers (pMDIs), including the high stability of dry powders, avoidance of propellant gases and ease of use. DPIs generate dry powder aerosols that deposit on the lung mucosa upon inhalation. In order to achieve the desired therapeutic outcome, drug particles must first dissolve in the lung lining fluids, then diffuse across these fluids to reach the epithelium and be absorbed. The fate of inhaled particles once deposited on the lung surfaces has not been yet fully understood. However, the particle physicochemical properties are believed to play a role on their dissolution, interaction with lung lining fluids and permeability across the lung epithelium. The main aim of this doctoral thesis was a better understanding of the relationships between drug particle physicochemical properties and their fate in the lung tissue in terms of dissolution and drug absorption. Increased knowledge in this area would indeed assist the development of novel and more effective inhaled medications. The first objective was the development and validation of a simple and low cost deposition system to apply aerosolised dry powder particles in a narrow size range and a controlled dose to both epithelial and non-epithelial lung models (Calu-3 cells grown at the air-liquid interface (ALI) and airway mucus) for in-vitro studies. The deposition system consisted of a vacuum desiccator fitted with a PennCentury Dry Powder Insufflator™ – Model DP-4 without the needle but equipped with a PennCentury Air Pump™ – Model AP-1 (Penn-Century. Inc. Wyndmoor, PA). We demonstrated that it was able to homogeneously disperse different types of dry powders (micronised and spray dried), and consistently deliver controlled doses of drug in a narrow particle size range (3-5 µm). However, the system presented a major limitation as no real separation between respirable (<10 μm) and non-respirable (>10 μm) particles could be achieved. The system was then exploited to investigate the effect of the formulation on drug absorption across Calu-3 cell layers. Salbutamol sulfate and indomethacin, respectively in class III (high solubility, low permeability) and II (low solubility and high permeability) of the Biopharmaceutical Classification System (BCS), were chosen as model dry powders. It was demonstrated that for both drugs, a dry powder formulation led to a faster absorption across Calu-3 layers than their solution counterpart. Indomethacin was more permeable than salbutamol in either case, proving that our system was capable of discriminating between drugs with different permeability profiles according to the BCS. Indomethacin low water solubility did not limit its absorption. Accordingly, the potential of novel indomethacin formulations produced by colleagues at University College London (UCL) as platforms to improve the absorption of poorly soluble drugs could not be appreciated. In the case of salbutamol, we attempted to gain a better understanding of its mechanism of absorption through the lung epithelium, particularly when delivered as a dry powder. The data showed that Organic Cation Transporters (OCT) are likely to contribute to salbutamol absorption when applied in solution, but no valid conclusions could be drawn when the drug was delivered as dry powder due to Calu-3 cell layers being disrupted during the course of the experiment. Finally, the role of mucus on salbutamol and indomethacin particle dissolution and drug absorption was investigated. A system consisting of a thin mucus layer coating Transwell® insert membranes was developed. Drug permeation across the mucus layer was monitored and compared with that across the Calu-3 cell layers. The rate of permeation of salbutamol sulfate and indomethacin across the three barriers investigated (clean Transwell® inserts, mucus layer and Calu-3 cell layers) followed an opposite order (clean insert > mucus layer > Calu-3 cell layer for salbutamol sulfate, Calu-3 cell layer > mucus layer > clean insert for indomethacin), demonstrating that the mucus was acting as a barrier in the case of salbutamol, but conversely promoted dissolution of indomethacin particles. A contribution to the clarification of the role of the mucus was made with the identification of some of the parameters that affect drug-mucus interaction: ionisation and lipophilicity. Solubility in water did not seem to have the same impact as for oral delivery. In this respect, we showed that the BCS, which only takes into account drug solubility and permeability, was a non-adequate description for the prediction of the behaviour of indomethacin in the lungs.